Hirschman’s Ideas as Evaluation Tools - Robert Picciotto (Journal of MultiDisciplinary Evaluation)
Background: Albert O. Hirschman, one of the most distinguished social scientist of the past half century, is not widely known within the evaluation community. Yet he practiced the art of evaluation without acknowledging it and the influential concepts that he generated are extremely valuable as evaluation tools.